The STUDY ON THE INTELLIGENT AGENT'S NOTIONAL ARCHITECTURE OF ARTIFICIAL INTELLIGENCE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Artificial Intelligence (AI) is a branch of science and engineering concerned with the theory and practice of creating systems that display the we identify with intelligence in human behaviour. Starting with a brief history of artificial intelligence, this paper provides a broad overview of this multidisciplinary field, organized around the main modules of an intelligent agent's notional architecture (knowledge representation; problem solving and planning; knowledge acquisition and learning; natural language, speech, and vision; action processing and robotics), which are highlighted both the main areas of artificial intelligence research, development and application